Discontinuing MRSA and VRE contact precautions: Defining hospital characteristics and infection prevention practices predicting safe de-escalation. (1st November 2022) - Martin, Elise M.; Colaianne, Bonnie; Bridge, Christine; Bilderback, Andrew; Tanner, Colleen; Wagester, Suzanne; Yassin, Mohamed; Pontzer, Raymond; Snyder, Graham M.
Abstract: Objective: To define conditions in which contact precautions can be safely discontinued for methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus (VRE). Design: Interrupted time series. Setting: 15 acute-care hospitals. Participants: Inpatients. Intervention: Contact precautions for endemic MRSA and VRE were discontinued in 12 intervention hospitals and continued at 3 nonintervention hospitals. Rates of MRSA and VRE healthcare-associated infections (HAIs) were collected for 12 months before and after. Trends in HAI rates were analyzed using Poisson regression. To predict conditions when contact precautions may be safely discontinued, selected baseline hospital characteristics and infection prevention practices were correlated with HAI rate changes, stratified by hospital. Results: Aggregated HAI rates from intervention hospitals before and after discontinuation of contact precautions were 0.14 and 0.15 MRSA HAI per 1, 000 patient days ( P = .74), 0.05 and 0.05 VRE HAI per 1, 000 patient days ( P = .96), and 0.04 and 0.04 MRSA laboratory-identified (LabID) events per 100 admissions ( P = .57). No statistically significant rate changes occurred between intervention and non-intervention hospitals. All successful hospitals had low baseline MRSA and VRE HAI rates and high hand hygiene adherence. We observed no correlations between rate changes after discontinuation and the assessed hospital characteristics and infection prevention factors, but the rate improved with higher proportion of semiprivate rooms ( P = .04). Conclusions: Discontinuing contact precautions for MRSA/VRE did not result in increased HAI rates, suggesting that contact precautions can be safely removed from diverse hospitals, including community hospitals and those with lower proportions of private rooms. Good hand hygiene and low baseline HAI rates may be conditions permissive of safe removal of contact precautions.